Presence of giant tiger shrimp Penaeus monodon (Fabricius, 1798) in eastern Península of Yucatan coast, Mexico - Wakida-Kusunoki,Armando T (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2016)
ABSTRACT. Giant tiger shrimp Penaeus monodon has been declared as an invader in the western coast of Atlantic Ocean. We report the first records of P. monodon in the eastern Peninsula of Yucatan, Mexico. On 14 October and 25 November 2014, three giant tiger shrimps were caught in Río Lagartos Lagoon. The total lengths of the shrimp were between 210 and 290 mm and weighed between 111.6 and 200 g. Further sampling and monitoring are required in other coastal lagoons in Yucatan State to assess the invasion area and the origin as well as the probable invasion route of this species.